Industrial restructuring and union power : micro-economic dimensions of economic restructuring and industrial relations in India - Mathur, Ajeet N.; Asian Regional Team for Employment Promotion; World Employment Programme ([New Delhi] : Asian Regional Team for Employment Promotion : World Employment Programme, 1991)
Examines how liberalization of trade regimes in India affects trade union power, and to what extent differences in oligopoly and product market competition affect the structure and behavior of the unions.
Includes bibliographical references (p. [159]-162) and index
oif 04/08/16
Loan
Keywords: Industrial relations; Labor unions; Industrial organization